Factors influencing online purchase intention among youth / Mohamad Rafiq Mohd Ridza - Mohd Ridza, Mohamad Rafiq (Faculty of Business and Management, 2019)
This research is conducted to determine the factors influencing online purchase intention among youth. The study was conducted by distributing uncounted sets of questionnaires, which all of it were being distributed conveniently to the youth in Malaysia. All the questionnaires were answered by respondent through Google form. The distribution of link of questionnaires was done from 1st of November until 30th of November 2019. Based on the data finding, it shows that two out of three independent variables which are perceived usefulness and perceived enjoyment have positive relationship towards the dependent variable, online purchase intention. Besides that, the hypothesis that were developed at the beginning stage of research process that is (H1) perceived ease of use has a significant relationship towards online purchase intention among youth, (H2) perceived usefulness has a significant relationship towards online purchase intention among youth and (H3) perceived enjoyment has a significant relationship towards online purchase intention among youth are supported as the result.